Weed Management in Sesame - Jason Ferrell; Ramon Leon (EDIS)
Sesame is a promising new crop for Florida, but few herbicides have been registered for it as yet. This 2-page fact sheet provides weed-control strategies for sesame. Written by Jason Ferrell and Ramon Leon, and published by the UF Department of Agronomy, June 2015. (Photo credit: Doug Mayo)